2019
DOI: 10.1136/bmjopen-2018-025606
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of home care nurse’s experiences in deprescribing of medications: a qualitative descriptive study

Abstract: ObjectivesThe aim of this study is to explore the barriers and enablers of deprescribing from the perspectives of home care nurses, as well as to conduct a scalability assessment of an educational plan to address the learning needs of home care nurses about deprescribing.MethodsThis study employed an exploratory qualitative descriptive research design, using scalability assessment from two focus groups with a total of 11 home care nurses in Ontario, Canada. Thematic analysis was used to derive themes about hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 16 publications
(22 reference statements)
3
41
0
2
Order By: Relevance
“…Previously studies reported that there are problems when transferring information between healthcare facilities and that this problem is critical when they intend to deprescribe medicines [30][31][32][33]. For this reason, the development of deprescribing approaches is essential for optimizing medication management and reducing polypharmacy in older adults [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Previously studies reported that there are problems when transferring information between healthcare facilities and that this problem is critical when they intend to deprescribe medicines [30][31][32][33]. For this reason, the development of deprescribing approaches is essential for optimizing medication management and reducing polypharmacy in older adults [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Although these barriers may exist, they can be overcome with strong, trustworthy multidisciplinary involvement to promote medication optimization. Providing education and training about interprofessional communication and collaboration within the nursing curriculum will allow geriatric nurses to develop effective communication skills and meaningful partnership to facilitate deprescribing conversations, as well as shared decision-making within the circle of care network involving older adults, caregivers, and health care professionals (Sun, Tahsin, Barakat-Haddad, et al, 2019).…”
Section: Multidisciplinary Collaborationmentioning
confidence: 99%
“…This includes the identification of inappropriate medication, creation of goals and/or plans to either halt or taper off the medication, proper observation, assessment, and patient teaching (Naughton & Hayes, 2016). However, based on past research, nurses often lack the knowledge (Lim et al, 2010), attitudes, and skills required to successfully support deprescribing practices (Hermanowski et al, 2016;Sun, Tahsin, Barakat-Haddad, et al, 2019). Incorporating deprescribing education at the undergraduate level may provide student nurses with the foundational knowledge related to polypharmacy and medication management, which in turn will equip the prospective nurses in developing the competency needed to advocate for and participate in the deprescribing process in their future practice.…”
mentioning
confidence: 99%
“…Our larger research initiative consisted of three phases: Phase 1, a scalability assessment which involved conducting focus group sessions to assess homecare nurses' learning needs about deprescribing of medications for older adults in the community; Phase 2, the development of a scale-up plan, including developing deprescribing learning modules based on focus group findings from Phase 1 to address homecare nurses' educational needs; and Phase 3, implementation of the scale-up educational plan to pilot-test the deprescribing learning modules with homecare nurses in Ontario, Canada. The study findings from Phase 1 and 2 were presented together and have been published (Sun, Tahsin, Barakat-Haddad et al, 2019).…”
Section: Study Design Setting and Samplingmentioning
confidence: 99%
“…Despite the existence of practice guidelines about safe medication management, researchers found that at least 25% of community dwelling, non-hospitalized, older adults experienced inappropriate prescriptions of medications from their health care providers (Reeve et al, 2013). Current literature highlights the risks of polypharmacy among older adults which necessitate the need for medication optimization and interprofessional collaboration to raise awareness about safety in medication management in the community (Sun, Tahsin, Barakat-Haddad et al, 2019). Deprescribing is an important way of optimizing medication management and reducing polypharmacy for older adults, which involves the process of tapering, adjusting or discontinuing medication when it is deemed inappropriate or is considered no longer medically necessary (…”
mentioning
confidence: 99%